Serine Protease Inhibitor Kazal Type 1, A Potential Biomarker for the Early Detection, Targeting, and Prediction of Response to Immune Checkpoint Blockade Therapies in Hepatocellular Carcinoma - Jia, Jianlong; Ga, Latai; Liu, Yang; Yang, Zhiyi; Wang, Yue; Guo, Xuanze; Ma, Ruichen; Liu, Ruonan; Li, Tianyou; Tang, Zeyao; Wang, Jun (Frontiers in Immunology, 2022)
Background: We aimed to characterize SPINK1 as a gene signature for early diagnosis, molecular targeting and prediction of ICB treatment response of HCC. Methods: The transcriptomics, proteomics and phenotype analyses were performed separately or in combination. Results: We obtained the following three findings about SPINK1 herein. Firstly, in the transcriptomic training data set which included stage I-II 279 tumor (out of 1884 stage I-IV HCC specimens) and 259 normal samples, we demonstrated that there were significantly AUC, IDI and NRI on HCC discrimination in SPINK1-involved models compared with AFP. The calibration of both SPINK1-participated curves was fitted significantly better than AFP. In the two independent transcriptomic validation data sets, which included stage I-II 201, 103 tumor and 192, 169 normal tissue specimens, respectively, the derived results were consistent with the above-described findings. In the proteomic training data set, that included stage I-II 98 tumor and 165 normal tissue samples, the analyses also revealed better AUC, increased IDI and NRI in the above SPINK1-associated settings. A moderate calibration was shown on both SPINK1-involved models, relative to the poor of AFP. Secondly, in vitro and/or in vivo murine models, the wet-lab experiments demonstrated that SPINK1 promoted the proliferation, clonal formation, migration, chemoresistance, anti-apoptosis, tumorigenesis and metastasis of HCC cells, while anti-SPINK1 antibody inhibited the growth of the cells, suggesting that SPINK1 possessed the ‘tumor-marker’ and ‘targetable’ characteristics in HCC control. The GO and KEGG analyses revealed that SPINK1 was engaged in immunity-related pathways including T cell activation. Thirdly, in the transcriptomic analyses of 368 HCC specimens from TCGA cohort, the high abundance of SPINK1 was positively correlated with the high levels of activated tumor-infiltrating CD4+, CD8+ T lymphocytes, dendritic and natural killer cells, while there were also positive correlations among SPINK1 and immune checkpoints including PD-1, LAG-3, TIM-3，TIGIT，HAVCR2 and CTLA-4, respectively. ESTIMATE algorithm calculated the positive correlations among SPINK1, Immune and Estimate scores that may possibly help in predicting the response of ICB therapies. Conclusions: SPINK1 could be likely served as a potential biomarker for early detection, targeting and prediction of ICB treatment response in HCC control.